PREFERÊNCIA DE Bracon vulgaris E ADEQUAÇÃO DE ALGUNS HOSPEDEIROS EM CONDIÇÕES DE LABORATÓRIO - Carvalho, Sérgio L.; Fernandes, Wedson D.; Habib, Mohamed E. M.; Patel, Prafulbala N. (REVISTA DE AGRICULTURA, 2015)
PREFERÊNCIA DE Bracon vulgaris E ADEQUAÇÃO DE ALGUNS HOSPEDEIROS EM CONDIÇÕES DE LABORATÓRIO